Implementasi Program Comprehensive Guidance And Counseling Dalam Pengembangan Potensi Siswa (Studi Kasus Di Smp Muhammadiyah Al-Kautsar Program Khusus Kartasura Sukoharjo Tahun Pelajaran 2015/2016) - Novitasari, Ambar; , Drs. Abdullah Mahmud, M.Ag (2016)
Every student has basic potentials given by Allah Swt to be able to develop and actualize in the life. Therefore, in the implementation of education, it needs to consider the potential of every student. Hence, in arranging the school programs, it can facilitate the students‟ needs which are appropriate to their potentials in the forms of spirituality, tendency, talent, intention, or intelligence. Therefore, the task of educators/teachers is not only focusing on the development of students‟ cognitive but also on the development of skill, emotional, social, and physical aspects of the students. SMP Muhammadiyah Al-Kautsar of Special Program of Kartasura Sukoharjo provides service in the form of comprehensive guidance or counseling to the students with purposes that each student is always in goodness and able to develop as well as to actualize all potentials they have maximally. The purposes of this research is to describe the implementation of the program of Comprehensive Guidance and Counseling in SMP Muhammadiyah Al-Kautsar of Special Program of Kartasura Sukoharjo in The Academic Year of 2015/2016, the roles and the tasks of the school personnel in the implementation of the program of Comprehensive Guidance and Counseling and its influence on the development of the students‟ potentials. This research is categorized in the field research using a qualitative approach. The data collection has used the methods of interview, observation, and documentation study. Meanwhile, the method of data analysis has used the descriptive qualitative analysis which is in the form of narration or paragraph and not in the form of numbers, through the process of data collection, data reduction, and data display. After that, the conclusion drawing has conducted by using the deductive method that is the way of thinking beginning from the theory which is then matched with the data. Based on the data analysis from the results of the research, it can be concluded that the implementation of the program of Comprehensive Guidance and Counseling in SMP Muhammadiyah Al-Kautsar of Special Program of Kartasura Sukoharjo includes 4 service components, they are: service of basic guidance, responsive service, service of individual planning, and system support which is covered in series of activities which have become the school programs, they are: Basic Competence Test, Mentoring, Academic Coaching and Consultation, Counseling Program, Home Visiting, and Out Door Program. It has been supported by Spiritual Guidance, Character Building, and Motivation Building Training in order that all students grow and develop in goodness and always have motivation to be better. Meanwhile, in the implementation, all school personnels collaborate each other in implementing their roles and tasks such as attending the conference meeting and building a harmonious relation to all students. Further, the program has been evaluated and monitored by the headmaster. The existence of the program of Comprehensive Guidance and Counseling can give an influence on the development of the students‟ potentials in SMP Muhammadiyah Al-Kautsar of Special Program of Kartasura Sukoharjo.